Culture-Based Da’wah Digitization to Strengthen Social Harmony in Religion on Plural Netizens - Risma Fahrul Amin; Zainuddin Zainuddin; Ari Wibowo (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This paper explained how the da'wah digitization which in this era was a major challenge that must be faced by plural netizens in Indonesia. To strengthen social harmony in religion, it was needed culture-based da'wah digitization, especially moderate da'wah to create netizens that would be able to interact well with one another on the internet. Social-religious harmony in cyberspace needed to be strengthened because with a strong social harmony in religion on plural netizens, the harmony of life between religious people or religious communities will be achieved and survived on the plural netizens in particular. The existence of supporting factors and inhibiting factors for the occurrence of social and religious harmony in the plural netizens showed that there was a relation between socio-religious harmony and culture-based da’wah digitization.